Aβ/Amyloid Precursor Protein-Induced Hyperexcitability and Dysregulation of Homeostatic Synaptic Plasticity in Neuron Models of Alzheimer’s Disease - Martinsson, Isak; Quintino, Luis; Garcia, Megg G.; Konings, Sabine C.; Torres-Garcia, Laura; Svanbergsson, Alexander; Stange, Oliver; England, Rebecca; Deierborg, Tomas; Li, Jia-Yi; Lundberg, Cecilia; Gouras, Gunnar K. (Frontiers in Aging Neuroscience, 2022)
Alzheimer’s disease (AD) is increasingly seen as a disease of synapses and diverse evidence has implicated the amyloid-β peptide (Aβ) in synapse damage. The molecular and cellular mechansism(s) by which Aβ and/or its precursor protein, the amyloid precursor protein (APP) can affect synapses remains unclear. Interstingly, early hyperexcitability has been described in human AD and mouse models of AD, which precedes later hypoactivity. Here we show that neurons in culture with either elevated levels of Aβ or with human APP mutated to prevent Aβ generation can both induce hyperactivity as detected by elevated calcium transient frequency and amplitude. Since homeostatic synaptic platicity (HSP) mechanisms normally maintain a setpoint of activity, we examined whether HSP was altered in AD transgenic neurons. Using methods known to induce HSP, we demonstrate that APP protein levels are regulated by chronic modulation of activity and that AD transgenic neurons have an impaired adaptation of calcium transients to global changes in activity. Further, AD transgenic compared to WT neurons failed to adjust the length of their axon initial segments (AIS), an adaptation known to alter excitability. Thus, we show that both APP and Aβ influence neuronal activity and that mechanisms of HSP are disrupted in primary neuron models of AD.